Association of Pneumatosis Intestinalis With Surgical Outcomes and Mortality: A Matched, Retrospective Cohort Study and Literature Review - Kyle D. Klingbeil, MD, MS; Hila Zelicha, PhD, RD; Yijun Chen, MD; Douglas S. Bell, MD; Edward H. Livingston, MD, FACS, AGAF (Annals of Surgery Open)
Background:. To determine the clinical importance of pneumatosis intestinalis (PI) on surgical decision-making and patient outcomes. Methods:. A matched cohort observational study was conducted including all clinical encounters for both ambulatory and inpatient care at UCLA Health between February 15, 2006 and January 31, 2023. Patients were initially identified using encounter diagnostic codes for “other specified diseases of intestine.” A radiologic diagnosis of PI was then assessed using natural language processing techniques followed by confirmation using manual chart review. Patients who did not have PI served as a control group. Patient comorbidity was assessed using Elixhauser comorbidity scores. Logistic regression and Cox hazard analyses were used to assess associations between PI and mortality. The main outcome was 90-day all-cause mortality. Secondary outcomes were the proportion of patients undergoing surgery and, of those, how many required bowel resections. Results:. Of the 16,728 patients identified by diagnostic coding, 315 were confirmed to have a diagnosis of PI. The 90-day mortality rate for all patients with PI was 29%. Surgery was performed for 62 patients (20%), of whom 46 (72%) underwent bowel resection and 16 (28%) underwent abdominal exploration alone. Most patients underwent surgery for peritonitis (37%), bowel obstruction (31%), and/or pneumoperitoneum (23%) in association with PI; whereas only 8% of patients received surgery exclusively for PI. There was no statistically significant association between PI and mortality with logistic regression conditioned on other risk factors for mortality. In contrast, survival analysis of a matched cohort demonstrated a small effect of PI on mortality (hazard ratio = 1.24: 95% confidence interval = 1.16–1.32, P = 0.021). Conclusions:. Most patients with a diagnosis of PI survive without requiring surgery. Of those who undergo surgery, nearly all have indications for laparotomy exclusive of PI. Mortality in patients who have pneumatosis is strongly associated with comorbid disease, with little to no independent association with PI. Our findings suggest that the presence of PI should not be a primary indication for surgical intervention.